Paxillus involutus-Facilitated Cd2+ Influx through Plasma Membrane Ca2+-Permeable Channels Is Stimulated by H2O2 and H+-ATPase in Ectomycorrhizal Populus × canescens under Cadmium Stress - Zhang, Yuhong; Sa, Gang; Zhang, Yinan; Zhu, Zhimei; Deng, Shurong; Sun, Jian; Li, Nianfei; Li, Jing; Yao, Jun; Zhao, Nan; Zhao, Rui; Ma, Xujun; et al. (Frontiers in Plant Science, 2017)
Using a Non-invasive Micro-test Technique, flux profiles of Cd2+, Ca2+, and H+ were investigated in axenically grown cultures of two strains of Paxillus involutus (MAJ and NAU), ectomycorrhizae formed by these fungi with the woody Cd2+-hyperaccumulator, Populus × canescens, and non-mycorrhizal (NM) roots. The influx of Cd2+ increased in fungal mycelia, NM and ectomycorrhizal (EM) roots upon a 40-min shock, after short-term (ST, 24 h), or long-term (LT, 7 days) exposure to a hydroponic environment of 50 μM CdCl2. Cd2+ treatments (shock, ST, and LT) decreased Ca2+ influx in NM and EM roots but led to an enhanced influx of Ca2+ in axenically grown EM cultures of the two P. involutus isolates. The susceptibility of Cd2+ flux to typical Ca2+ channel blockers (LaCl3, GdCl3, verapamil, and TEA) in fungal mycelia and poplar roots indicated that the Cd2+ entry occurred mainly through Ca2+-permeable channels in the plasma membrane (PM). Cd2+ treatment resulted in H2O2 production. H2O2 exposure accelerated the entry of Cd2+ and Ca2+ in NM and EM roots. Cd2+ further stimulated H+ pumping activity benefiting NM and EM roots to maintain an acidic environment, which favored the entry of Cd2+ across the PM. A scavenger of reactive oxygen species, DMTU, and an inhibitor of PM H+-ATPase, orthovanadate, decreased Ca2+ and Cd2+ influx in NM and EM roots, suggesting that the entry of Cd2+ through Ca2+-permeable channels is stimulated by H2O2 and H+ pumps. Compared to NM roots, EM roots exhibited higher Cd2+-fluxes under shock, ST, and LT Cd2+ treatments. We conclude that ectomycorrhizal P. × canescens roots retained a pronounced H2O2 production and a high H+-pumping activity, which activated PM Ca2+ channels and thus facilitated a high influx of Cd2+ under Cd2+ stress.